Variação na produção de mel por colmeias de abelhas Africanizadas em função da época de introdução de rainhas jovens - Carbonari, Vladson [UNESP]; Malaspina, Osmar [UNESP]; Alves Junior, Valter Vieira; Polatto, Leandro Pereira (FapUNIFESP (SciELO), 2016)
The objective of this research was to evaluate the honey production per hive and the egg laying rates of queens produced in 2007, 2008 and 2010. Thirty colonies initiated with a queen per colony at each climatic season were used during the three years. The years, started on January (summer), April (autumn), July (winter) and October (spring) and ended 12 months later, at the same periods related to each season of the later years. Honey supply were weighed before and after centrifugation to evaluate the quantity of the stored honey. Colonies with queens introduced during autumn and winter in the three years produced 57.2±6.0kg and 60.7±7.5kg of honey, respectively. In the first year of production activity, after the introduction of queens in the initial colonies, values were significantly higher than those obtained in colonies with queens introduced in the summer (39.3±7.6kg) and spring (41.8±3.7kg). Egg laying rates of queens were higher in spring (98.2±3.9%) and summer (88.4±7%), indicating greater food flow (flowerings) in these seasons compared to the averages in autumn (30.3±8.1%) and winter (24.5±7.2%). Produce and introduce queens of Africanized Apis mellifera in colonies initiated during autumn and winter was found to be economically feasible. Honey production of colonies initiated in these periods were higher and they had greater population stability in times of scarcity of flowerings.
Variation in honey yield per hive of Africanized bees depending on the introducing time of young queens
Keywords: Apiculture; Climatic season; Egg laying rate